Regulation of forager honey bee appetite independent of the glucose-insulin signaling pathway - Ghanem, Saleh; Akülkü, İrem; Güzle, Kübra; Khan, Zaeema; Mayack, Christopher (Frontiers in Insect Science, 2024)
To maintain energetic homeostasis the energetic state of the individual needs to communicate with appetite regulatory mechanisms on a regular basis. Although hunger levels indicated by the energetic state and appetite levels, the desire for food intake, tend to be correlated, and on their own are well studied, how the two cross-talk and regulate one another is less known. Insects, in contrast to vertebrates, tend to have trehalose as the primary sugar found in the hemolymph, which could possibly serve as an alternative monitor of the energetic state in comparison to the glucose-insulin signaling pathway, found in vertebrates. We investigate how manipulating hemolymph sugar levels alter the biogenic amines in the honey bee brain, appetite levels, and insulin like peptide gene expression, across three age classes, to determine how the energetic state of the honey bee might be connected to appetite regulation. We found that only in the forager bees, with a lowering of hemolymph trehalose levels, there was an increase in octopamine and a decrease in tyramine levels in the honey bee brain that corresponded with increased appetite levels, while there was no significant changes in ILP gene expression. Our findings suggest that hemolymph trehalose levels aid in regulating appetite levels, in forager bees, via octopamine and tyramine, and this regulation appears to be functioning independent of the glucose insulin signaling pathway. Whether this potentially more direct and rapid appetite regulatory pathway can be generalized to other insects, which also undergo energy demanding activities, remains to be investigated.